the hard boys mystery stories 51 : the masked monkey - Dixon, Franklin W.; Franklin W. Dixon (New York Grosset & Dunlap, Inc, 1972)
In The Masked Monkey (#51), Frank and Joe Hardy travel to Brazil to locate the missing son of a wealthy industrialist. The brothers uncover a dangerous criminal organization specializing in identity alteration and face exotic threats, including a trained killer monkey. Key clues are provided by Chet Morton$1 (Bs hobby of retrieving golf balls. s
English